2021
DOI: 10.1038/s42005-021-00718-w
|View full text |Cite
|
Sign up to set email alerts
|

Particle-hole asymmetry in the dynamical spin and charge responses of corner-shared 1D cuprates

Abstract: Although many experiments imply that oxygen orbitals play an essential role in the high-temperature superconducting cuprates, their precise role in collective spin and charge excitations and superconductivity is not yet fully understood. Here, we study the doping-dependent dynamical spin and charge structure factors of single and multi-orbital (pd) models for doped one-dimensional corner-shared spin-chain cuprates using several numerically exact methods. In doing so, we determine the orbital composition of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 71 publications
5
16
0
Order By: Relevance
“…Such splitting is similar to what has been observed at stronger coupling strengths for charge excitations in 1D Hubbard chains due to the formation of a gap. [47] We note that multiple peaks only occur for densities near or below the van Hove point. Recent Raman experiments have suggested that the pseudogap phenomenon might terminate at the density associated with the Lifshitz point [48] which for a weakly coupled system coincides with the van Hove singularity.…”
Section: Discussionmentioning
confidence: 77%
“…Such splitting is similar to what has been observed at stronger coupling strengths for charge excitations in 1D Hubbard chains due to the formation of a gap. [47] We note that multiple peaks only occur for densities near or below the van Hove point. Recent Raman experiments have suggested that the pseudogap phenomenon might terminate at the density associated with the Lifshitz point [48] which for a weakly coupled system coincides with the van Hove singularity.…”
Section: Discussionmentioning
confidence: 77%
“…In particular, the broad class of determinant QMC (DQMC) methods have proven highly effective in helping to characterize various correlated phases that arise as a result of interactions [1]. Perhaps most notably, DQMC has enabled the study of electron-electron interactions in the repulsive Hubbard model, where Mott insulator physics, magnetic order, unconventional superconductivity, and various additional correlation effects have been observed [2][3][4][5][6][7][8][9][10]. The sign problem, however, has severely limited our ability to simulate systems absent particle-hole or other symmetries, giving rise to an effective computational cost that scales exponentially with system size and inverse temperature [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…We solve this model using exact diagonalization (ED) and determinant quantum Monte Carlo (DQMC), which provide numerically exact results on finite-size clusters. (Here, we can run DQMC simulations at comparatively low temperatures due to a mildler sign problem compared to 2D [53,54].) Focusing on half-filling, we find that the system has a narrow window of coupling strengths where it supports a q = π/a bond ordering.…”
mentioning
confidence: 98%
“…(For details of the method, we refer the reader to Refs. [53] and [46].) We now include the individual atomic motion of each 2p x orbital along the chain direction.…”
mentioning
confidence: 99%
See 1 more Smart Citation